CONTINUITY AND DEVELOPMENT OF IDEAS OF DEVELOPMENTAL LEARNING IN MATHEMATICAL EDUCATION: PRIMARY AND BASIC SCHOOL (Conferencea, 2024)
The article is devoted to the analysis of the problems of succession and continuity in mathematical education between primary and secondary schools. Methodological approaches to the study of numerical systems, as well as issues of forming conceptual thinking and developing students are considered. The main directions of the methodology for studying natural numbers and fractions are described, ensuring the unity of the logic of presentation and methodological approaches. Particular attention is paid to the development of a system of educational tasks that contribute to the systematization of knowledge and skills of schoolchildren. Based on the analysis of psychological, pedagogical and methodological literature, the specificity of the concept of continuity as a necessary condition for developmental learning aimed at forming mathematical literacy and functional competence of students is highlighted.